LOCUS OF CONTROL IN GEORGIAN POPULATION WHILE THE 2020 CORONAVIRUS PANDEMIC - Bzhalava, T.I.; Imedadze, I.V.; Sakvarelidze, R.T.; Tsulukidze , A.G. (Modern Psychology, 2021)
One of the factors affecting the behaviour in the conditions of COVID19 pandemic and, in its turn, responding these conditions, is the locus of control. Presented study aims to identify the locus of contol in pandemic situation and explore whether the stressful situation will affects the locus control type. The research uses an adapted (for Georgian population), standardized and validated Rotter Test and its modified version (by R. Sakvarelidze) where reference to the pandemic appears in every statement of the test. The subjects were tested using both versions. Main result of the study shows that in pandemic conditions people tend to change their locus of control-in most cases they become more internals than they used to be. The study also revealed that the external locus of control was substituted by the internal one. Such a change of the locus of control results in taking more personal responsibility for fulfiling the recommendations given by professionals from medical sphere. Consequently, psychological recommendation will involve promoting the qualities which are characteristic for internals. We suppose that obtained results will help us to develop the strategies for psychocorrection and psychorehabilitation during pandemic and post-pandemic period.
Keywords: COVID-19 pandemic; locus of contol; Rotter Test and its modified version